A functional MMP-9-1562C>T polymorphism, MMP-9 serum levels and nephrolithiasis risk in a southern Chinese population - Ding, Qi; Cao, Cheng; Shi, Ying; Fan, Zhijiang; Li, Feng; Tu, Wenjian; Jin, Xiaohua; Zhu, Hailiang; Fan, Bo (Frontiers in Medicine, 2023)
Background: The role of matrix metalloproteinase 9 (MMP-9) in the pathophysiology of chronic kidney disease (CKD), which is associated with a nearly two-fold greater risk for urinary calculi compared to people without CKD, has been demonstrated. The aim of the research is to evaluate the association between MMP-9-1562C>T polymorphism, MMP-9 serum levels and nephrolithiasis risk. Methods: A hospital-based case-control study involving 302 kidney stone patients and 408 controls without kidney stone from southern China was conducted. Sanger sequencing was used to genotype the MMP-9-1562C>T polymorphism. The serum MMP-9 was measured in 105 kidney stone patients and 77 controls by ELISA assay. Results: Compared to the control group, the CT genotype was more frequent in nephrolithiasis patients (adjusted OR = 1.60, 95% CI = 1.09-2.37: the risk of developing nephrolithiasis in individuals with CT genotype compared to CC genotype). Moreover, there was also a higher frequency of CT/TT genotypes among patients with nephrolithiasis (adjusted OR = 1.49, 95% CI = 1.02-2.19: the risk of developing nephrolithiasis in individuals with CT/TT genotypes compared to CC genotype). The risk remained for the subgroups of patients aged ＞ 53, smokers with pack-years of smoking＞20, non-drinkers, non-diabetic patients, patients with hypertension, recurrent episodes and calcium oxalate stones (OR = 2.26, 95%CI = 1.31-3.91; OR = 5.47 , 95%CI = 1.10-27.30; OR = 1.76, 95%CI = 1.14-2.72; OR = 1.54 , 95%CI = 1.03-2.30; OR = 1.97, 95%CI = 1.01-3.82; OR = 1.67, 95%CI = 1.06-2.62; OR = 1.54, 95%CI = 1.02-2.32, respectively). Clinical biochemical parameters did not differ between genotypes. Compared to controls (18.57 ± 5.80 ng/ml), nephrolithiasis patients had significantly higher serum MMP-9 levels (30.17 ± 6.78 ng/ml, P < 0.001). The serum MMP-9 levels of patients with CT/TT genotypes of MMP-9-1562C>T was significantly higher than those with CC genotype (32.00 ±6.33 vs. 29.13 ± 6.85ng/ml, P = 0.037). Conclusions: The MMP-9-1562C>T polymorphism in association with its soluble protein increased the risk of kidney stone, thus suggesting it could be used as a susceptibility biomarker for nephrolithiasis. Further functional studies and larger studies that include environmental exposure data are needed to confirm the findings.